Is Trade Openness a Supportive Instrument for Human Development: A New Look on Newly Industrialized Economies - Tufail Hussain; Teguh Yudo Wicaksono (Universitas Negeri Malang, 2025)
Formulating policies to enhance human well-being requires an urgent need to understand the drivers of human well-being. Therefore, the current study has proposed the socio and economic factors to investigate the main and moderate role of trade openness on Human Development for newly industrialized economies over 1990-2021. Current study shows the association between gross national income, urbanization, trade openness, labor force participation, foreign direct investment, and financial development. This study employs the fully modified and dynamic ordinary least square for the reliable outcome. Empirical findings show that gross national income, urbanization, financial development, and labor force participation increase human development. Likewise, the long-term association of FDI has an insignificant impact on human development. Moreover, the main effect of trade openness significantly contributes to human development. In contrast, the moderate effect of openness with financial development and labor force shows a significant improvement in human development. Similarly, the moderate effect with FDI shows an insignificant contribution to human development. This study proposes the imperative policy implications for the NIC economies to boost human development.